Analysis of Factors Affecting Brain Metastasis in Limited-Stage Small-Cell Lung Cancer Treated With Definitive Thoracic Irradiation - Wu, Shuting; Wang, Jiezhong; Zhang, Wei; Li, Jiancheng; Wu, Haishan; Huang, Zhiyu; Zhou, Guangrun; Pan, Jianji; Chen, Mingqiu (Frontiers in Oncology, 2020)
Background Small-cell lung cancer (SCLC) is the most lethal cancer. With the development of chemotherapy and radiotherapy, brain metastasis (BM) emerged as one most predominant treatment failure. However, the factors affecting BM have not been identified completely. The purpose of this study was to investigate the risk factors involved in the development of BM in patients with limited-stage small-cell lung cancer (LS-SCLC) following definitive thoracic radiotherapy (TRT) and to provide a reference for the planning of a clinical treatment strategy. Methods The clinical data of patients with LS-SCLC treated with neoadjuvant chemotherapy (NAC) followed by TRT were collected and retrospectively reviewed. The factors affecting BM, BM-free survival (BMFS) and overall survival (OS) rates were analyzed statistically. Results A total of 152 patients with LS-SCLC fulfilled the inclusion criteria were reviewed. Following TRT, 31 (20.4%) patients achieved CR, 90 (59.2%) patients reached PR, 31 (20.4%) patients maintained SD, and no patients developed PD. The OS at 1, 3, and 5 years was 80.6, 34.2, and 19.4%, respectively. Multivariate analyses indicated that the greatest dimension of primary tumor (Dmax-T) and short-term response to TRT were risk factors affecting BM. The clinical N stage (cN), greatest dimension of metastatic nodes (Dmax-N), short-term response to TRT, and adjuvant chemotherapy (AC) were identified as independent factors correlated with OS. Conclusions Poor short-term response to TRT and huger Dmax-T were risk factors for BM. AC following TRT improved patient survival, but not decreased BM. However, due to the limitations associated with the retrospective design of the present study, further prospective clinical trials are required to confirm these conclusions.